FROG DANCE: ART LEARNING FOR HYPERACTIVE AUTISM CHILDREN - Tri Wahyu Martiningsih; Fabiola Dharmawanti; Warih Handayaningrum (Universitas Sebelas Maret)
The purpose of this study was to analyze the strategy and learning outcomes of frog dance in hyperactive autism childrens at Inclusive PAUD Anggrek Mandiri school in Situbondo. The approach of this study is a qualitatif study with interview and observation as tools research. The participations of this study are two autism childrens. The result shows that learning strategy of frog dance performed by teacher using storytelling and imitation method with group model in inclusion class. Frog-dance learning’s results improved on the development of physical, intellectual, social, and emotional aspects.